Conferences, Communication and BIALL: a Whistle-Stop Tour of the 90s. (June 2019) - Maher, Michael
Abstract : This was the decade of the IT office revolution which would have a profound impact on working practices within law firms, including the library. The first, and arguably biggest, change was the creation of the World Wide Web by Tim Berners-Lee in 1991. The first law firm website was set up in 1994, and by the end of the decade virtually all law firms were using this as the key way to present their offerings. The first text message was sent in 1992. In 1994 Amazon was founded, as a source for buying books! By 1996 we were able to organize our contacts and diaries on a PalmPilot. Google was founded in 1998.